The Impact of Toll Road Infrastructure Development Policy in Cipali for Social Economic Changes in The Majalengka District - Entang Adhy Muhtar; Darto Miradhia; Rd. Ahmad Buchari; Riki Satia Muharam (Iapa Proceedings Conference, 2021)
The toll road development policy of Cikopo-Palimanan tends to have an impact on changes in the social and economic conditions of the people targeted and outside the development target. On the other hand, the impact on the economy includes how employment patterns, business growth, and investment. Therefore in this study it is important to analyze How the Impact and Strategy of the Infrastructure development of the Cipali toll road generated in Majalengka District. The research method used was descriptive qualitative method with the determination of informants. The results of the study are that the impact of toll road infrastructure development on socio-economic changes, especially in mapping in Majalengka Regency with 3 research locations, in general, the changes lead to positive changes, this can be seen from economic growth above 6% per year, the industrial sector and investment are growing very rapidly, there is stretching of the economy, especially the informal sector which is increasingly dynamic. However, it is recognized that in some sectors of infrastructure development it does not necessarily mean that the community will immediately feel the benefits.